From Likes to Investments: The Mediating Role of Herding Behaviour Between Finfluencer Exposure, Digital Financial Literacy, and Gen Z’s Digital Investment Decisions - Faradisa Bachmid; Hartaty Hadady; Muhammad Asril Arilaha (Journal of International Conference Proceedings, 2025)
The rapid development of digital investment platforms and social media has transformed how Generation Z investors in Indonesia obtain financial information and make investment decisions. This study investigates the mediating role of herding behaviour in the relationships between finfluencer exposure, digital financial literacy, and digital investment decisions. A quantitative method was applied using an online survey of 280 Generation Z investors who actively use platforms such as Bibit, Ajaib, Bareksa, Pluang, and Pintu. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS to assess direct and indirect effects. The findings show that finfluencer exposure positively influences herding behaviour and digital investment decisions. Digital financial literacy negatively affects herding behaviour but positively influences digital investment decisions. Herding behaviour also positively affects digital investment decisions and significantly mediates both the finfluencer exposure–decision and literacy–decision relationships. These results highlight that social influence and financial competence jointly shape the investment behaviour of young digital investors. This study contributes to behavioural finance literature and offers implications for policymakers, educators, and digital investment platforms to strengthen financial literacy while managing social media influence.